Recent advances of curcumin and its analogues in breast cancer prevention and treatment. Issue 92 (8th October 2015) - Mock, Charlotta D.; Jordan, Brian C.; Selvam, Chelliah
<x xml:space="preserve">Abstract</x> This review focuses on recent developments in the use of curcumin, curcumin analogues, and novel delivery systems as a preventive and therapeutic method for breast cancer treatment.